1996
DOI: 10.1016/0735-1097(95)00465-3
|View full text |Cite
|
Sign up to set email alerts
|

Flow-mediated vasodilation of human epicardial coronary arteries: effect of inhibition of nitric oxide synthesis

Abstract: Our data suggest that nitric oxide modulates basal coronary artery tone but that mediators other than nitric oxide may be responsible for the flow-mediated vasodilation of human epicardial coronary arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 30 publications
3
41
0
1
Order By: Relevance
“…These stressors induce coronary vasodilatation by a primarily endothelium-independent mechanism. In fact, only the subsequent increment in coronary blood flow triggers further flow-induced vasodilation, which is endothelium-dependent (13). In the present study, we demonstrate that the non-pharmacological stressor CPT is able to reveal a reduced CFR in SHypo patients.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These stressors induce coronary vasodilatation by a primarily endothelium-independent mechanism. In fact, only the subsequent increment in coronary blood flow triggers further flow-induced vasodilation, which is endothelium-dependent (13). In the present study, we demonstrate that the non-pharmacological stressor CPT is able to reveal a reduced CFR in SHypo patients.…”
Section: Discussionsupporting
confidence: 53%
“…In the second study, dipyridamole infusion induced a similar reduction of hyperemic coronary flow, and thus of CFR, in patients with SHypo and in normal subjects (12). It is noteworthy that both adenosine and dipyridamole induce a hyperemic stimulus that relaxes vascular smooth muscle cells in a fashion only partially dependent on endothelial function (13).…”
Section: Introductionmentioning
confidence: 92%
“…12 Such an adenosine-induced increase in sympathetic nervous activity might be particularly marked with the large dose of adenosine used in our study. This is in contrast to studies in which small amounts of adenosine have been administered directly into the coronary arteries, 23,24 not yielding systemic concentrations high enough to increase sympathetic nervous activity. Therefore, a low level of sympathetic nervous activity could be an explanation for the lack of effect of NO synthase inhibition on adenosine-induced coronary vascular resistance observed in these studies.…”
Section: Discussionmentioning
confidence: 42%
“…ATP is a potent vasodilator of the coronary microvasculature, 1 but also dilates epicardial coronary arteries, through flowmediated vasodilation. 24 In addition, ATP infusion did not cause any significant changes in ST deviation or changes in the double (rate-pressure) product in the present study. Second, it has been shown that the presence of coronary endothelial dysfunction at the level of resistance vessels and/or conduit vessels can cause perfusion defects in patients without significant coronary stenosis.…”
Section: Mechanisms Responsible For Reversible Defects In Patients Wisupporting
confidence: 44%